2010
DOI: 10.1007/s13277-010-0111-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-dependent regulation of PTEN after arsenic trioxide treatment in bladder cancer cell line T24

Abstract: Arsenic trioxide has shown remarkable biological activity against bladder cancer in some clinical studies. However, the mechanism of its action is unknown. Our aim was to find the relationship between miRNAs and arsenic trioxide treatment by using T24 human bladder carcinoma cells. By performing microRNA microarray and quantitative real-time PCR after ATO treatment, we found that expression levels of several miRNAs, in particular, miRNA-19a, were significantly decreased in T24 cell line. Furthermore, cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…[31] Knockdown of miR-19a also inhibited cell growth and induced cell apoptosis. [32] miR-19a is predicted to target the 3′ untranslated region of PTEN and BIM mRNA. Our study supports the notion that the levels of PTEN and BIM were downregulated in CM treated with Exo GATA-4 .…”
Section: Discussionmentioning
confidence: 99%
“…[31] Knockdown of miR-19a also inhibited cell growth and induced cell apoptosis. [32] miR-19a is predicted to target the 3′ untranslated region of PTEN and BIM mRNA. Our study supports the notion that the levels of PTEN and BIM were downregulated in CM treated with Exo GATA-4 .…”
Section: Discussionmentioning
confidence: 99%
“…Other miRNAs, such as anti-miR-21 and miR-15a/16-l, were reported to enhance the sensitivity of leukemic cells to the anti-cancer effect of As 2 O 3 and all-trans retinoic acid [23,24,25]. However, little attention has been paid to the role of miRNAs in the process of apoptosis induced by As 2 O 3 in APL patients.…”
Section: Introductionmentioning
confidence: 99%
“…37 A similar study was conducted by Bollati et al regarding the influence of cadmium on miRNA-146a expression. 38,39 Bisphenol A is a compound that plays an essential role in the production of plastic masses used in the fast-food industry. Awissar-Whiting et al have reported changes in the expression of miRNA-21, miRNA-335, and miRNA-153 after interactions with this compound.…”
Section: Mirnas In Toxicologymentioning
confidence: 99%